IMPLEMENTASI METODE BOOTSTRAP UNTUK PENGUJIAN HIPOTESIS MENGENAI DUA MEAN POPULASI - Suparman, Suparman (Jurnal Ilmiah AdMathEdu, 2012)
This paper examines the problem of testing hypotheses about two population means. Most testing hypotheses about two population means, based on the assumption that each random sample drawn from a normal population. In this paper studied the problem of testing hypotheses about two population means are not using the assumption of normality and homogeneity. The method used to test hypotheses about two population means are the bootstrap method. The basic idea of the bootstrap method of repeated sampling with replacement from the sample data. Replication of samples used to determine the point estimator of Achieved Significance Level (ASL). Performance of the bootstrap method was tested using simulated data. The test results show that the bootstrap method to test the hypothesis of two population means well. Furthermore bootstrap method implemented on real data.